2014
DOI: 10.3174/ajnr.a3960
|View full text |Cite
|
Sign up to set email alerts
|

Brain Parenchymal Signal Abnormalities Associated with Developmental Venous Anomalies in Children and Young Adults

Abstract: BACKGROUND AND PURPOSE:Abnormal signal in the drainage territory of developmental venous anomalies has been well described in adults but has been incompletely investigated in children. This study was performed to evaluate the prevalence of brain parenchymal abnormalities subjacent to developmental venous anomalies in children and young adults, correlating with subject age and developmental venous anomaly morphology and location.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 22 publications
1
20
0
Order By: Relevance
“…These findings are not significantly different from ours with 83% supratentorial location, 64% drainage to peripheral veins, and a collecting vein diameter range of 0.8 -3.0 mm (median, 1.8 mm). We found associated T2 signal changes in the parenchyma adjacent to the DVA in 26% of the DVAs, which is within the range of those reported in different studies: 7.8%, 10 11.6%, 8 and 28%. 11 The phenotypic similarities of the DVAs in our study group compared with those reported in the general population exclude morphologic unique features of this vascular malformation in CMMRD patients.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These findings are not significantly different from ours with 83% supratentorial location, 64% drainage to peripheral veins, and a collecting vein diameter range of 0.8 -3.0 mm (median, 1.8 mm). We found associated T2 signal changes in the parenchyma adjacent to the DVA in 26% of the DVAs, which is within the range of those reported in different studies: 7.8%, 10 11.6%, 8 and 28%. 11 The phenotypic similarities of the DVAs in our study group compared with those reported in the general population exclude morphologic unique features of this vascular malformation in CMMRD patients.…”
Section: Discussionsupporting
confidence: 90%
“…Two or more DVAs coexisting in separate regions of the brain were observed in 7%-16% of described patients with DVAs. 8,9 Most DVAs are asymptomatic and are found incidentally. However, DVAs have been documented as a rare cause of cerebrovascular bleeding and ischemic events.…”
mentioning
confidence: 99%
“…23 These associations suggest that DVA development is not solely a reaction to focal abnormalities of venous drainage but may also be a consequence of widespread perturbations of vascular development. Recent reports have identified associated parenchymal signal abnormalities in 11.6% of children and young adults 9 and in 12.5% of older adults 8 with DVAs, suggesting that the altered drainage they provide may have consequences on the surrounding brain. All of these associations lend credence to concerns that DVAs may have a deleterious impact on the surrounding brain or may be a harbinger of more widespread abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…2 DVAs are typically considered variants of venous development that, in and of themselves, are of little clinical import. However, a small percentage of DVAs have been associated with such findings as cavernous malformations, 3,4 thrombosis with subsequent venous infarction, 5,6 lobar atrophy, 7 T2 and FLAIR signal-intensity abnormalities, 8,9 perfusion abnormalities, 10,11 and SWI hypointensities. 12 In our daily pediatric neuroradiology practice, we had noticed a high prevalence of presumed incidental DVAs in our oncology patient population.…”
mentioning
confidence: 99%
“…DVAs are believed to form after an insult during embryogenesis or development and represent venous drainage variations in which medullary veins drain through a collecting vein to the pial veins, a dural venous sinus, or deep ependymal veins . Greater than half of all DVAs in both children and adults drain into the deep venous system . The majority of DVAs are located supratentorially within the frontal lobe, and when located infratentorially, the majority are within the cerebellum …”
Section: Cerebral Vascular Malformationsmentioning
confidence: 99%